2003
DOI: 10.1111/j.1651-2227.2003.tb02504.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E treatment on the oxidative damage occurring in Henoch‐Schönlein purpura

Abstract: Aim: To evaluate the role of reactive oxygen molecules (ROMs) in the pathogenesis of Henoch‐Schonlein purpura and the effect of vitamin E on oxidative damage. ROMs have been suggested to contribute in many pathological conditions including renal diseases and vasculitis. Methods: The activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH‐Px) as antioxidant enzymes were measured, and the level of malondialdehyde (MDA) as an indicator of lipid peroxidation in 27 children with Henoch‐Schönlein pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…Studies performed in China and other countries have shown that the incidence of HSP is related to oxidative damage and an imbalance in antioxidant protection [19]. Oxidative stress, especially lipid peroxidation, plays an important role in the renal damage of HSP [12]. Exogenous CP increases the stability of the cell membrane by reducing the production of oxygen radicals and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in China and other countries have shown that the incidence of HSP is related to oxidative damage and an imbalance in antioxidant protection [19]. Oxidative stress, especially lipid peroxidation, plays an important role in the renal damage of HSP [12]. Exogenous CP increases the stability of the cell membrane by reducing the production of oxygen radicals and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma MDA values were very similar between our groups, suggesting no significant tissue damage in children with episodic FUO. It is important to note that both erythrocyte and plasma MDA values were assessed in the afebrile phase, because lipid peroxidation products are often found in inflammatory diseases and show significantly higher values in the acute period of disease than in remission (12,24,25). The significant positive correlation of erythrocyte MDA with AOPP and albumins in our study may indicate elevated ROS levels in the febrile phase of episodic FUO and their modifying effects on lipids and proteins in this phase.…”
Section: Discussionmentioning
confidence: 59%
“…Some protective mechanisms exist to limit free-radical tissue injury. Protective mechanisms consist of antioxidant enzymes, which inhibit free-radical reactions and freeradical scavengers, e.g., vitamin E and C and β-carotene [11]. The significantly lower activity of antioxidant enzyme ARYL at disease onset and considerable increase in remission suggest that antioxidant enzyme is depleted as a compensation for protection from hazardous effects of increased ROS in the active phase.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism has a crucial and probably causative role in the pathogenesis of various acute and chronic diseases, including inflammation, renal failure, and cardiovascular damage [3][4][5]. Experimental studies on oxidative injury have been carried out in glomerular diseases and vasculitis [6][7][8]; however, clinical investigations on oxidative stress in HSP are scarce [9][10][11].…”
Section: Introductionmentioning
confidence: 99%